(untitled) (Fiep Bulletin - online, 2014)
This study aimed at verifying changes in anthropometric, metabolic and hemodynamic parameters in a male population, 25-35 year old, submitted to a strength training program. Sample comprised a 10-man Intervention Group (IG) and a 15-man Control Group (CG), all voluntary with no weight training participation over three previous years. Intervention was carried out for 20 weeks, on a three weekly session basis, 90 minutes each, a total of 60 training sessions. We measured Percent of Body Fat (%BF), Fat Body Mass (FBM) and Lean Body Mass (LBM), Resting Systolic Blood Pressure (RSBP) and Diastolic (DBP), Maximal Systolic Blood Pressure (MSBP), Maximal Heart Rate (MHR), Maximum Cardiac Output (MCO), Maximum Systolic Volume (MSV) and Maximum Oxygen Uptake (VO2MAX). Interpreting anthropometric, metabolic and hemodynamic parameters observed, the conclusion is that a strength training program leads to small improvements in all parameters, and some are relevant (RSBP and DBP), suggesting that this kind of program is useful for 25-35 year-old males.